Thioredoxin-interacting protein is an independent risk stratifier for breast ductal carcinoma in situ. (December 2018) - Miligy, Islam; Gorringe, Kylie; Toss, Michael; Al-Kawaz, Abdulbaqi; Simpson, Peter; Diez-Rodriguez, Maria; Nolan, Christopher; Ellis, Ian; Green, Andrew; Rakha, Emad
Abstract Current clinicopathological parameters are useful predictors of breast ductal carcinoma in situ behavior, but they are insufficient to define high-risk patients for disease progression precisely. Thioredoxin-interacting protein (TXNIP) is a key player of oxidative stress. This study aims to evaluate the role of TXNIP as a predictor of ductal carcinoma in situ progression. Tissue microarrays from 776 pure ductal carcinoma in situ and 239 mixed ductal carcinoma in situ and invasive tumors were constructed. All patients were treated at a single institution with a long-term follow-up and TXNIP expression was assessed using immunohistochemistry. TXNIP expression was investigated in terms of associations with clinicopathological and molecular features and patient outcome. Loss/reduced cytoplasmic expression of TXNIP was associated with features of aggressiveness including high nuclear grade (p = 1.6 × 10−5 ), presence of comedo necrosis (p = 0.001), and estrogen receptor negative (ER−)/HER2− ductal carcinoma in situ (p = 4.6 × 10−5 ). Univariate analysis showed an inverse association between TXNIP expression and outcome in terms of shorter local recurrence-free survival (p = 0.009). Multivariable analyses showed that independent predictors of ductal carcinoma in situ recurrence were low TXNIP expression (p = 0.005, HR = 0.51, and 95% CI: 0.32–0.81), larger ductal carcinoma in situ size, and high nuclear grade. TXNIP functions as a tumor suppressor gene with loss of its expression associated with ductal carcinoma in situ recurrence. TXNIP can be used as a potentially useful marker in prognostic stratification of ductal carcinoma in situ for management decisions.